Art illuminations in 18th – 19th centuries manuscripts from Ngayogyakarta Hadiningrat Palace as a creative industry development - Ariesa Pandanwangi; Sophia Himatul Alya; Iman Budiman; Arleti Mochtar Apin; Tessa Eka Darmayanti (Cogent Arts & Humanities, 2023)
AbstractMost of the classical Javanese manuscripts are stored in the palace, scattered in various places, and countries, and many of which have not been returned by the country that took them during the colonial period. The manuscript contains the history and philosophy of Javanese life with extraordinary illustrations of illumination decorations on each page. Based on this phenomenon, this research was designed to explore the potential of Javanese manuscripts of the 18th and 19th centuries that can be developed into batik motifs and benefit the creative industry. Through these manuscripts, it is expected that they can support the development of batik motifs and enrich Indonesian batik. The research employs the descriptive qualitative research method. The data is collected through five stages: observation, recording, collection of manuscripts, literature study, and interviews. This qualitative research uses a descriptive approach to comprehensively understand the research subject. This study concludes that the illumination of classical Javanese manuscripts always contains meaning and carries the ideology of the Javanese people at that time, potentially developed into batik motifs. Through batik motifs based on classical Javanese script, it is hoped that they can enrich Indonesian batik motifs and can be implemented in the creative industries. This could enrich Indonesian batik patterns that can be used directly in the creative industry. Also, accordance to the UU No 5/2010 regarding to preserve cultural heritage valuable object older than 50 years should be properly carried without disregard sustainability aspects.